A promising ZnO/Graphene van der Waals heterojunction as solar cell devices: A first-principles study. (November 2022) - Gong, Aina; Feng, Yue; Liu, Chi; Chen, Jiaojiao; Wang, Zhenjia; Shen, Tao
Abstract: The electronic structure of two-dimensional (2D) materials in van der Waals heterojunctions also appears extensive theoretical research, we use DFT-D2 theory to calculate the energy band, density of states, formation energy, work function, charge density difference, optical properties, and our theoretical calculations show that there is no electrons and holes redistribution at the intrinsic ZnO composite graphene interface, ZnO vacancy defects and doping not only make electron–hole good separation, but also a significant increase in the UV absorption intensity and range. We analyze the effects of the electron–hole pair separation at the heterogeneous junction interface by combining the work function and the movement of the Dirac point. We found that when defected ZnO composite graphene, there is the maximum formation energy, the value is 5.4eV, the largest moving distance of the Fermi level, 0.73eV, and the maximum absorption strength and range of UV light. This 2D van der Waals heterojunction provides a promising prospect for electrons, photovoltaic, solar cell.